Voltage Stability Analysis of Radial Distribution Networks - Ranjan, R.; Das, D. (2003)
The paper presents voltage stability analysis of radial distribution networks. A new stability index is proposed to identify the nodes that are on the verge of voltage collapse. The value of the proposed voltage stability index is calculated at each node of the network. A modified load flow method is used for voltage stability analysis. The modified load flow method incorporates composite load modeling and variations in load pattern at each node. The results are compared with the other known methods of voltage sensitivity indices and found satisfactory. A comprehensive comparison with the recently proposed voltage stability index by Chakravorty and Das [1] is presented in this paper. A detailed analysis of effects of different load models on voltage computation and voltage stability are carried out, and it is observed that for voltage stability analysis, a constant impedance load model can be used without losing the sensitivity of load modeling.